Impacts of future climate change on water ecosystem services in the watershed of river Homem (Northwest Portugal) - Escobar Juipa, Emanuel Nestor (2019)
Descargue el texto completo en el repositorio institucional de la Universidade do Porto: https://hdl.handle.net/10216/121239